PENGARUH FEAR OF COVID, ELECTRONIC WORD OFMOUTH DAN BRAND IMAGE TERHADAP MINATRESERVASI HOTEL DI BALI SECARA ONLINE - Ahmad Salman Alfarisi (2023)
The"study aims to prove and analyze the influence of fear of covid, electronic word of mouth and brand image on the interest of hotel reservations in Bali online."This research is quantitative by distributing questionnaires to 92 respondents who are interested in buying (reservations) hotels in Bali in the Greater Jakarta area. This study used the Partial Least Square (PLS) method with the Smart-PLS 3.0 program. The results of data analysis show that Fear Of Covid does not have a significant effect on the interest in lodging reservations in Bali online. These results prove that fear of covid who has anxiety arising from seeing a danger that threatens him. This requires that E-Wom which has positive comments from social media users, product choice information, product quality information, information about prices offered, information about the security of internet networking site transactions, and recommendations from social media users can influence the interest in booking hotel lodging in Bali online. E-Word Of Mouth and Brand Image influence the interest in lodging reservations in Bali online. This is blinding by having positive comments from social media users, product choice information, product quality information, information about prices offered, information about the security of internet networking site transactions, and recommendations from social media users can influence the interest of hotel lodging reservations in Bali online